Defining the economic value of the ecosystems loss in Ria de Aveiro - Mustricu, Zoe Steliana (2012)
Coastal zones, bathing 84% of the countries of the world, are important ecosystems that facilitate leisure, recreational and tourism activities, host strategic ports of commerce and provide opportunities for permanent living for the population. The interest in generating information about the coastal ecosystems’ status in ecological, economic and social terms, has only risen in the last decade and at the moment, attempts to quantify their economic valuation brings an important contribution to management plans, as well as to wetland conservation approaches. The main objective of the present thesis is to assess the economic value of the ecosystems found in the Ria de Aveiro Lagoon, as well as to compare some of the main research and action plans that were implemented in the area in the past ten years. The economic valuation was based, firstly, on a research on the existing bibliography, in order to identify the methods used and the associated values for certain ecosystems. Second, after defining the study area and highlighting the main approaches in term of management plans and programmes, were analyzed the changes and transfers of land use that took place from 1990 to 2006, having applied the economic values. The Ria de Aveiro brings an important contribution to the local economy and to the environment and in the past twenty years the human pressure has left a strong mark upon it. However, the latest interventions aimed at promoting the preservation, rehabilitation and recovery of the most sensitive areas, socially and economically, as well as environmentally. The purpose of this work is to ascertain the real losses of natural ecosystems in the Ria de Aveiro and translating them into economic terms.